Analisis Validitas Media Book Creator Menggunakan Model Problem Based Learning Pada Mata Pelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar - Fajriah Okta Vera; Reinita Reinita (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Learning media is a means or tool to convey information from teachers to students. Based on the results of observations and interviews that have been conducted in several elementary schools, problems were found, namely that students easily get bored in learning and teachers have difficulty in choosing appropriate learning media so that researchers developed digital learning media based on Book Creator with the aim of being able to overcome problems in schools and improve student learning outcomes. This research is a development research or R&D with the ADDIE model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. The validity test of Book Creator was carried out in 3 aspects, namely the material aspect, the media aspect, and the language aspect. The material validity test obtained a result of 88% with very valid criteria, the media validity test obtained a result of 92% with very valid criteria, and the language validity test with a result of 86.67% with very valid criteria. The calculation of the final validity results obtained a result of 88.89% with a very valid category. So that the Book Creator media can be used in the Pancasila Education learning process in grade V of elementary school.